Postmarket safety of drugs approved by Health Canada on the basis of clinical and surrogate outcomes: a cohort study - Lexchin, Joel (CMAJ Open, 2015)
BACKGROUND: Health Canada approves drugs on the basis of evidence from clinical trials using clinical or surrogate outcomes. This study compares the postmarket safety of these 2 groups of drugs. METHODS: Information about whether clinical or surrogate outcomes were used and the date of market approval were obtained from Health Canada’s Summary Basis of Decision documents issued from Jan. 1, 2005, to Dec. 31, 2014. Safety warnings and the dates they were issued were identified through advisories on the MedEffect Canada website. Kaplan–Meier survival curves were calculated to determine the likelihood that drugs in the clinical and surrogate outcome groups would receive a serious safety warning. The time from market authorization to first serious safety warning was compared for the 2 groups of drugs. RESULTS: A total of 124 drugs were approved by Health Canada using clinical outcomes and 114 using surrogate outcomes. Kaplan–Meier curves did not differ between the 2 groups (p < 0.9). The median time from market authorization to first serious safety warning was 722 days in the clinical outcome group and 818 days in the surrogate outcome group (difference 96 days, 95% confidence interval –295 to 425). INTERPRETATION: We found no statistically significant difference in postmarket safety between drugs approved using clinical outcomes and those approved using surrogate outcomes. Because drugs in the surrogate outcome group are approved before their benefit:harm ratio is fully established, these drugs should be used with caution until their clinical benefits are better understood.